1954
DOI: 10.1172/jci102929
|View full text |Cite
|
Sign up to set email alerts
|

Blood Volume Alterations in Congestive Heart Failure

Abstract: A considerable body of data indicates that the plasma volume, as measured by dye dilution methods, is generally increased in congestive heart failure (1-4). However, recent investigations, utilizing p82 (5, 6) or Cr51 (7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

1955
1955
2001
2001

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 26 publications
2
11
0
1
Order By: Relevance
“…No significant difference was noted in the four preparations used. Plasma volumes obtained by extrapolating iodine counts to zero time were likewise similar to those obtained by others when radioalbumin was used (40). Indeed, in two subjects Evans blue plasma volume determinations were within 8 per cent of the isotope dilution volumes.…”
Section: Miethodssupporting
confidence: 84%
“…No significant difference was noted in the four preparations used. Plasma volumes obtained by extrapolating iodine counts to zero time were likewise similar to those obtained by others when radioalbumin was used (40). Indeed, in two subjects Evans blue plasma volume determinations were within 8 per cent of the isotope dilution volumes.…”
Section: Miethodssupporting
confidence: 84%
“…Schreiber, Bauman, Yalow, and Berson (6) have reported that the mean ratio of body to venous hematocrit is .937 in control patients, .868 in patients with congestive heart failure, and .908 in patients free of failure. These differences in ratio imply that, where a tagged red cell method is used to determine total blood volume, comparisons between control patients, cardiac patients in congestive heart failure, and cardiac patients in the compensated state would be in error.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the patients had received meralluride (Meeuhydrin) 3 and 12 hours before the study. Three of the failure patients were female whereas all of the control patients were male.…”
Section: Selection Of Patientsmentioning
confidence: 99%